Focus on Analogies, Anecdotes and Paradoxes for Enhancing Effectiveness of Teaching-Some Examples in Fluid Mechanics - Madhu Murthy, K. (Journal of Engineering Education Transformations, 2006)
He who can, does; he who cannot, teaches. This mischievous statement is attributed to George Bernard Shaw who must have meant it in the lighter vein. Anybody can teach, some say; this uncharitable view is often expressed by people who look down upon the teaching profession.